Study of Sites of Lesion in Ischemic Stroke and Intracerebral Hemorrhage (Bangladesh Journal of Neuroscience, 2014)
Methodology: This retrospective cross sectional observational study was carried out in the Department of Neurology and Department of Medicine of Dhaka Medical College Hospital. (DMCH), during March, 2010 to February, 2011 in patients admitted with a history of first ever stroke. The duration of the study was one year .For this purpose, a total number of 140 patients, of which 70 were included in ischemic stroke and 70 in intracerebral haemorrhage group. CT scan of head of each patient was done at least 6 hours after the onset of the event .CT diagnosed cases of infarct and ICH were included in this study and subarachnoid haemorrhage cases were excluded. CT negative cases were further investigated by MRI brain when the clinical suspicions of stroke were strong.Results: The mean age of the patients having features of ischemic stroke and intracerebral haemorrhage were 59.81±11.08 and 57.21±10.09 respectively. Male female ratio was 1.92:1 and 1.69:1 in IS group and ICH group respectively. Regarding the risk factor hypertension and smoking were observed most common risk factors in the study patients in both groups. However, diabetes mellitus, arrhythmia, ischemic heart disease and dyslipidemia were observed more common in patients of ischemic stroke than ICH patients. Among the studied patients, ischemic stroke was observed more common in parietal region (20% of patients), internal capsule/ capsular region (17.14% of patients) and caudate nucleus region (10% of patients). ICH was observed most frequently 32.86% (n=23), 15.71% (n=11) and 5.71% (n=4) in lentiform nucleus/putamen, thalamus and combined gangliothalamic region respectively. In both group left sided lesion prevailed more than right side. In case of ischemic strokes, left side lesion was 61.43% .In intracerebral haemorrhage, left side lesion was 58.57%. It was also observed that deep intracerebral haemorrhage is the most common location (74.29%) than the lobar region (25.71%).Conclusion: Site of predilection of lesions and their distribution pattern differ in ischemic stroke and intracerebral haemorrhage. This study revealed that infarcts were more common in parietal and capsular region and haemorrhage were more common in putamen, thalamus and combined gangliothalamic regions. Ischemic stroke and ICH also have differences in clinical presentation and risk factor profile.Bangladesh Journal of Neuroscience 2014; Vol. 30 (2): 69-76